Respostas

2013-10-30T02:06:40-02:00
(a + 3b, 2a + b) = (5a + 2, 2b)

Nota-se que parece com pontos x,y de sistema de cartesianas, então temos:

(a + 3b, 2a + b) = (5a + 2, 2b)
     x             y              x       y

Portanto, efetuando:
a + 3b = 5a + 2  =>  -4a +3b = 2
2a + b = 2b        =>  b = 2a

Então, substituindo:
-4a + 3.(2a) = 2   =>   -4a + 6a = 2   =>   a = 1
E sendo assim:
b = 2a   =>   b = 2

Substituindo em (a + 3b, 2a + b) = (5a + 2, 2b), fica:
(1 + 3.2, 2.1 + 2) = (5.1 + 2, 2.2)   =>   (7, 4) = (7, 4)
1 5 1